Preparation, modelling, characterization and release profile of vitamin D3 nanoemulsion. (1st November 2022) - Jan, Yasmeena; Al-Keridis, Lamya Ahmed; Malik, Muneeb; Haq, Afrozul; Ahmad, Sayeed; Kaur, Jasmeet; Adnan, Mohd; Alshammari, Nawaf; Ashraf, Syed Amir; Panda, Bibhu Prasad
Abstract: Vitamin D is a lipophilic molecule, thus susceptible to ultraviolet light, oxygen and processing conditions. The poor stability and dispersibility in food matrices make it further unavailable in the low-/nonfat foods. In this study, a low temperature aided sonication method was used for incorporating vitamin D3 in the oil-in-water emulsion. The emulsion system was fabricated by blending medium-chain triglyceride (MCT), ethylene glycol (EG), Kolliphor-RH-40 (KRH-40), vitamin-D3 and aqueous phase, followed by optimization using Box Behnken design (BBD) tool of Response Surface Methodology (RSM). The RSM revealed that the sonication time of 30 s, stirring rate of 1500 rpm, mixing time of 10 min, 600 μL of KRH-40, 100 μL of MCT and 400 μL of EG produced the optimum nanoemulsion with mean particle size (169 nm), zeta potential (−22.6 mV), turbidity (1.78) and encapsulation efficiency (91%). Differential scanning calorimetry thermograms and Fourier transform infrared spectra indicated no chemical interaction between active component and surfactants. Scanning electron microscopy revealed irregular shapes. HPLC results indicated a slight decrease (3000 ± 130.58 IU to 1703.66 ± 28.09 IU) in vitamin D3 concentration over three months of storage. The fabricated nanoemulsion will open new horizons in the fortification of vitamin D in non-/low fat food matrices. Graphical abstract: Schematic representation of methodology. Image 1 Highlights: Vitamin D3 nano emulsion fabricated by low temperature sonication method. Optimized parameters for fabrication of Vitamin D3 nano emulsion system. Kolliphor & ethylene glycol with MCT is best for Vitamin D3 nano emulsion system. Vitamin D3 nano emulsion is suitable for incorporation into food matrices.